UKURAN PERUSAHAAN MEMODERASI PENGARUH ANTARA LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KONDISI FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022) - Yuliandari, Amanda; Andy Dwi Bayu Bawono (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to investigate the effects of leverage, liquidity, and profitability on the likelihood of financial distress, incorporating firm size as a moderating factor. The analysis focuses on companies operating within the consumer non-cyclical sector that were listed on the Indonesia Stock Exchange during the period from 2020 to 2022. Out of a total population of 129 firms, 113 were selected using purposive sampling techniques. The data were subjected to classical assumption testing and analyzed with the assistance of SPSS software. The results reveal that leverage and profitability significantly influence financial distress, while liquidity does not show a meaningful statistical effect. In addition, company size cannot moderate the effect between leverage, liquidity, and profitability on financial distress.